The Influence Of Discipline, Leadership Style And Work Environment On Employee Performance Through Motivation At The Secretariat General Of The DPR RI - Edi Setiawan; Herry Krisnandi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to analyze the performance of employees in the Secretariat of the Indonesian House of Representatives (DPR RI). Data collection was conducted by distributing questionnaires to respondents using purposive sampling method. The respondents in this study were employees of the Secretariat of the DPR RI. A total of 167 responses were successfully obtained from the distribution of questionnaires to DPR RI Secretariat employees. The collected data were then analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS 22 software. Based on the AMOS analysis, the following results were obtained: 1) Work discipline has a positive and significant influence on motivation. 2) Leadership style has a positive and significant influence on motivation. 3) Work environment has a positive and significant influence on motivation. 4) Work discipline has a positive and significant influence on employee performance. 5) Leadership style has a positive but not significant influence on employee performance. 6) Work environment has a positive but not significant influence on employee performance. 7) Work motivation has a positive and significant influence on employee performance. 8) Work discipline has a positive and significant influence on employee performance through motivation. 9) Leadership style has a positive and significant influence on employee performance through motivation. The work environment has a positive and significant influence on employee performance through motivation.